2015
DOI: 10.1021/acssuschemeng.5b00994
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Production of Carbon Fiber: Effect of Cross-Linking in Wool Fiber on Carbon Yields and Morphologies of Derived Carbon Fiber

Abstract: Currently, most of the carbon fibers are made from unsustainable fossil fuel-based precursors including high purity polyacrylonitrile (PAN) and pitch. High purity PAN is not only more expensive than wool fiber but also a limited quantity is produced because of global shortage of its monomer. In this work, various cross-linking pathways are explored as a means of altering the yield and tensile properties of carbon fiber derived from the carbonization of cross-linked wool fiber at 800°C under nitrogen. A range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Preliminary research showed that wool fibres can replace the synthetic polymer in the sight of carbon fibre production. Hassan et al [46] found that carbon fibres were able to be produced through the carbonization of untreated and crosslinked wool fibre. The carbon yield of the resulting fibres was found to be a function of the type of crosslinking agents applied to wool.…”
Section: Application Of Sheep Wool In Cement-based Compositesmentioning
confidence: 99%
“…Preliminary research showed that wool fibres can replace the synthetic polymer in the sight of carbon fibre production. Hassan et al [46] found that carbon fibres were able to be produced through the carbonization of untreated and crosslinked wool fibre. The carbon yield of the resulting fibres was found to be a function of the type of crosslinking agents applied to wool.…”
Section: Application Of Sheep Wool In Cement-based Compositesmentioning
confidence: 99%
“…The use of ACF have been extended to multiple processes based on adsorption and catalysis, such as gas separation, wastewater purification, advanced oxidation processes, and supercapacitors [15][16][17][18][19]. Nowadays the CF, as well as ACF, production is based on the use of petroleum derivatives as precursor materials, which implies high-energy demands and a major contribution to the carbon footprint [20,21]. These problems could be minimized by using a precursor material from a renewable source; many studies had already used biomass as an ACF precursor, and in other cases natural fibres, such as silk, jute, cotton, or bamboo, have been used [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Yet the drawback is the high cost associated to their extraction from plants, along with the high-energy demand of the melt spinning process for the fabrication of the fibres [11]. On the other hand, scarce studies report the use of natural fibres from animal origin (e.g., wool) as precursors of carbon fibres [12]. Despite the carbon content of wool is lower than that of polyacrylonitrile and other biomass-derived precursors (e.g., lignin, cellulose); due to their high protein content they are rich in heteroatoms, which could represent an advantage for particular purposes.…”
Section: Introductionmentioning
confidence: 99%
“…This new spatial disposition prevents the fusion of the fibres during further thermal treatments at high temperatures [11]. The mechanisms involved during the oxidative stabilisation of wool fibres are not yet clarified, as most of the studies have focused on their use for the preparation of highly porous activated carbon fibres [14], fabrics [12], and felts [15].…”
Section: Introductionmentioning
confidence: 99%